DNA damage-induced cell death： lessons from the central nervous system - Borges, Helena Lobo; Linden, Rafael; Wang, Jean YJ (Cell research, 2008)
DNA damage can, but does not always, induce cell death. While several pathways linking DNA damage signals to mitochondria-dependent and -independent death machineries have been elucidated, the connectivity of these pathways is subject to regulation by multiple other factors that are not well understood. We have proposed two conceptual models to explain the delayed and variable cell death response to DNA damage： integrative surveillance versus autonomous pathways. In this review, we discuss how these two models may explain the in vivo regulation of cell death induced by ionizing radiation （IR） in the developing central nervous system, where the death response is regulated by radiation dose, cell cycle status and neuronal development.